2018
DOI: 10.1021/acs.jpcc.8b03372
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic and Postsynthetic Chemistry of M4AuxAg44–x(p-MBA)30Alloy Nanoparticles

Abstract: Metal heteroatom substitution in molecular nanoparticles offers a unique opportunity to study alloying with an unprecedented level of detail and control, which may be important for applications in optics, electronics, medicine, and catalysis. Many examples of single- or few-heteroatom substitutions exist in molecular nanoparticles, but true alloys with compositions varying over a wide range of substitutions are rare. Here, we study M4Au x Ag44–x (p-MBA)30 alloy nanoparticles as a model system, where M is a cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 49 publications
(84 reference statements)
1
25
0
Order By: Relevance
“…Our theoretical calculation also demonstrates that the interaction energy between the central atom and the Ag 12 shell in 2 is larger than that in 1 (Table S1†). In addition, electrophilicity of gold atoms is also accountable for the stabilization of heteronuclear nanoclusters 38…”
Section: Resultsmentioning
confidence: 99%
“…Our theoretical calculation also demonstrates that the interaction energy between the central atom and the Ag 12 shell in 2 is larger than that in 1 (Table S1†). In addition, electrophilicity of gold atoms is also accountable for the stabilization of heteronuclear nanoclusters 38…”
Section: Resultsmentioning
confidence: 99%
“…[56,57] This illustrates that [Ag 44 [57] The groups of Xie, Pradeep, and Kappes, and Bigioni independently reported the synthesis of [Ag 44Àx Au x (SR) 30 ] 4À alloy NCs (n = 0-12;S R = p-MBA or SPhF). [89,102,195] In the same paper,X ie et al [89] also reportedt he synthesis of [Ag 44Àx Cu x (p-MBA) 30 ] 4À alloy NCs (x = 0-6). .…”
Section: [Agmentioning
confidence: 91%
“…Silver and gold mix readily to form the naturally occurring alloy electrum and therefore the study of mixtures of silver and gold within these MPCs is of interest (Yang et al, 2013). Mixtures of M 4 Au x Ag 44-x (p-MBA) 30 MPCs can be obtained by co-reducing silver and gold polymers of p-MBA, where 0 x 12 (Conn et al, 2018). Gold-rich species have been synthesized and then thermally processed to destroy the species that contained fewer gold atoms, thereby enriching the samples in M 4 Au 12 Ag 32 (p-MBA) 30 MPCs.…”
Section: Chemical Contextmentioning
confidence: 99%
“…Furthermore, gold is known to be more electronegative and more noble than silver, so the gold atoms are expected to assume positions within the structure where they can possess the lowest oxidation state among the metal atoms. Bader analysis (Bader, 1990;Tang et al, 2009) of the electron distribution in M 4 Ag 44 (p-MBA) 30 has shown that atoms in the inner icosahedral core have an oxidation state of zero (Conn et al, 2015;Yang et al, 2013) whereas in M 4 Au 12 Ag 32 (p-MBA) 30 those atoms are slightly reduced (Conn et al, 2018). The other metal atoms were found to be oxidized, with their oxidation states increasing with distance from the center of the molecule.…”
Section: Structural Commentarymentioning
confidence: 99%